The Effect of Scaffolding Using the Peer Tutoring Method on Biology Learning Outcomes in the Material of the Human Excretory System - Widia Astuti; Marta H Sianipar (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To find out the effect of scaffolding using the peer tutoring learning method on the cognitive, affective and psychomotor aspects of class IX students of SMP Negeri 1 Muaro Jambi on the subject of the excretory system in humans. Methodology: This type of research is a real experiment or true experiment. While the research design used in this study is the Posttest-Only Control Design. The sample in this study was class IX A as the experimental class and class IX D as the control class. The types of data and data sources in this study are quantitative data obtained from the results of tests carried out or data that describe cognitive aspects and qualitative data, namely data obtained from affective and psychomotor aspects. The instrument used for assessing learning outcomes in the cognitive aspect is a written test. Multiple choice questions are used for the posttest in the experimental class and the control class. For the assessment of learning outcomes on the affective aspect a questionnaire was used, and for the assessment of learning outcomes on the psychomotor aspect a worksheet was used for students. Main Findings: Scaffolding (providing assistance) using the Peer Tuthoring learning method does not affect the learning outcomes of biology in class IX students of SMP Negeri 1 Muara Jambi in the cognitive aspect, but affects the affective and psychomotor aspects. Novelty/Originality of this study: It can be used as material for consideration and information for teachers in selecting appropriate, effective, and efficient learning models in the biology learning process. So that it can improve student learning outcomes in Biology subjects.